The story of sexual identity narrative perspectives on the gay and lesbian life course - Hammack, Phillip L.; Cohler, Bertram J. (New York ; Oxford : Oxford University Press, 2009)
In examining the shifting narratives of sexual identity in the 20th and 21st centuries and their impact on the process of human social development, this edited volume fuses historical cultural, and psychological perspectives on human sexuality to articulate a rigorous interdisciplinary approach to the study of sexual lives.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Gender identity -- History; Gay and lesbian studies; Homosexuality -- History; Lesbianism -- History; Sex role; Sex differences